(untitled) (Research, Society and Development, 2020)
This research was developed with the objective of evaluating the teaching and learning of students about wind energy and project feasibility, in technical courses of integrated high school, through Ausubel’s Theory of Meaningful Learning. An educational product was used to quantify the results, in the form of a smartphone application, which was called “Direct Wind”. This application is intended to provide the technical and economic feasibility of wind farm investment projects in Brazil, based on technical and financial data. For the application of this product, a Workshop was held with a general presentation of technical themes, the application and calculations of project feasibility. As a result, it was found through research with students that the dynamics allowed the learning to be meaningful and built new knowledge. It was concluded that the educational product can be used in the classroom as an auxiliary tool for teaching and learning wind energy, confirming the applicability of Ausubel’s Meaningful Learning Theory.